Process and properties of the carbon nanotube assisted LiCoO2 thin-film battery electrode by pulsed laser deposition - Lo, An-Ya; Sun, Chuan-Shu; Tseng, Wen-Shou; Kuo, Cheng-Tzu (My University, 2009)
In this study, a pulsed laser deposition process was developed to deposit a carbon nanotube (CNT) assisted LiCoO2 electrode to improve its power density. The electrodes were deposited on Pt-coated Si substrates with Ar and O-2 as sputtering gases and LiCoO2+C as the target. The results indicate that the working pressure is the most important parameter to control the composition of the electrode. Therefore, electrodes with a three-layer structure (i.e., LiCoO2-rich/CNT-rich/LiCoO2-rich) were fabricated by a three-step deposition process by varying the pressures from 13 to 1.3x10(4) Pa and then 13 Pa again, and it was found that the charge/discharge capacity became approximately 1.5 times greater than that in the corresponding electrode without a CNT-rich layer. The results also indicate that a higher substrate temperature is favorable for improving the crystallinity of the electrode to approach LiCoO2 crystals.
Keywords: carbon nanotubes; electrochemical electrodes; lithium compounds; pulsed laser deposition; secondary cells